THE USE OF DIGITAL TECHNOLOGIES TO PREPARE FUTURE TRANSLATORS - Khamidov Bekhruz Ziyot ugli (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The integration of digital technologies in translator education is essential for equipping future professionals with the skills needed to navigate the evolving translation landscape. This study explores the role of computer-assisted translation (CAT) tools, artificial intelligence (AI) applications, and virtual exchange programs in enhancing translator training. It examines both the benefits and challenges of incorporating these technologies into educational programs and assesses their impact on students’ professional preparedness. The findings underscore the importance of digital literacy, adaptive learning, and industry-aligned curricula in developing competent, technology-savvy translators ready to meet the demands of a rapidly changing industry.